Intensive training program for ultrasound diagnosis of adnexal masses: protocol and preliminary results. (9th July 2013) - Alcázar, J. L.; Díaz, L.; Flórez, P.; Guerriero, S.; Jurado, M.
ABSTRACT Objective To assess the feasibility of a specific training program for ultrasound diagnosis of adnexal masses. Methods A 2‐month intensive training program was developed. The program protocol consisted of a 1‐day intensive theoretical course focused on clinical and sonographic issues related to adnexal masses and ovarian cancer, followed by a 4‐week real‐time ultrasound training program in a tertiary center (25–30 adnexal masses evaluated per month) and a final 4‐week period for offline assessment of three‐dimensional (3D) volumes from adnexal masses. In this final period, each trainee evaluated five sets of 100 3D volumes. 3D volumes contained gray‐scale and power Doppler information, and the trainee was provided with clinical data for each case (patient age, menopausal status and reported symptoms). 3D volumes were obtained from surgically removed masses that had undergone histological diagnosis or from masses that had been followed up until resolution. After assessment of each set, the trainee's diagnostic performance was calculated (sensitivity and specificity) and each incorrectly classified mass was evaluated with the trainer. The objective was to achieve a sensitivity of > 95% and a specificity of > 90%. Learning curve cumulative summation (LC‐CUSUM) graphs were plotted to assess the learning curve for the trainees. Results One trainer and two trainees with little experience in gynecological ultrasound (one gynecologist and one radiologist) participated in this study. LC‐CUSUM graphs showed that competence was achieved after 170 or 185 examinations. The objectives for diagnostic performance were achieved after assessment of the second set of 3D volumes (200 cases) for each trainee. Conclusions The proposed training program appears to be feasible. High diagnostic performance can be achieved after analysis of 200 cases and maintained thereafter. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.